PENDIDIKAN ANTI KEKERASAN UNTUK ANAK USIA DINI: KONSEPSI DAN IMPLEMENTASINYA - Setiani, Riris Eka (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2016)
Anti-violence education basically seeks to answer the issues raised lately relation to the increasingly widespread child abuse both within the family, society, and the more so in an educational environment. Acts of violence, whatever its form, can harm children, which affected my growth and development both concerning aspects of physical, cognitive, emotional and psycho-social. Early childhood, is the age at which the child is experiencing rapid growth and development in both the development of emotional, intellectual, and moral language, or commonly the golden age. Therefore, in an effort to maintain and ensure the growth and development of AU goes well and unavoidable acts of violence perpetrated by adults importance of education applied nuanced nati violence. In the implementation, presenting the anti-violence education systems and processes that are safe, comfortable, fun and free of actions that lead to violence.